Analysis of Research Development on the Use of Internet of Things (IoT) Technology in Health Monitoring - Muhammad Azhar Irwansyah; Bambang Winardi; Budi Mardikawati; Dito Anurogo (Westscience Press, 2023)
Health monitoring is one of the many industries that has been transformed by the Internet of Things' (IoT) explosive growth. A thorough bibliometric analysis, cluster analysis, and term occurrences analysis are used in this study to reveal the complex world of IoT technology in health monitoring. Thematic groups are shown by cluster analysis, essential insights are provided by highly cited publications, and key concepts are clarified by word occurrences. The multidisciplinary aspect of research is exemplified by collaborative networks, prominent contributions, and rising trends within the literature. The amalgamation of results offers a comprehensive comprehension of the present condition of IoT in health monitoring, steering forthcoming research directions and promoting sustained innovation at the nexus of technology and healthcare.